2019
DOI: 10.1016/j.appet.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of sensory sensitivity in predicting food selectivity and food preferences in children with Tourette syndrome

Abstract: The role of sensory sensitivity in predicting food selectivity and food preferences in children with Tourette syndrome,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 45 publications
5
16
0
Order By: Relevance
“…Only children with ASD were found to show a lower preference for vegetables compared to children with TD. Consistent with previous research, children with TS and children with ASD were found to show lower preference for fruit in comparison to children who were TD (Smith et al, 2019;Maclin, Kandiah, Haroldson, & Khubchandani, 2017). The lack of ADHD preference effect Increased food fussiness and reduced fruit and vegetable preference, across TS and ASD, could lead to an unvaried diet with many adverse health implications.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Only children with ASD were found to show a lower preference for vegetables compared to children with TD. Consistent with previous research, children with TS and children with ASD were found to show lower preference for fruit in comparison to children who were TD (Smith et al, 2019;Maclin, Kandiah, Haroldson, & Khubchandani, 2017). The lack of ADHD preference effect Increased food fussiness and reduced fruit and vegetable preference, across TS and ASD, could lead to an unvaried diet with many adverse health implications.…”
Section: Discussionsupporting
confidence: 83%
“…Given the comorbidity between TS, ASD and ADHD, it is important to understand whether the underlying causes of food fussiness is syndrome specific or the shared pathologies across the three neurodevelopmental disorders accounts for the high levels of food fussiness evidenced in these groups of children (Smith, Rogers, Blissett & Ludlow, 2019). One potential explanation for food fussiness is the associated pathologies unique to the disorder.…”
Section: Deficit Hyperactivity Disorder [Adhd] Autism Spectrum Disormentioning
confidence: 99%
See 1 more Smart Citation
“…25 subjects had comorbid conditions, though none in the sample had been diagnosed with ASD. Caregivers of children with TS reported their children having greater sensory sensitivities to food, greater food selectivity, and decreased consumption of dairy, vegetables, and fruit ( Robbins, 2018; Smith et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Developing effective treatment requires knowledge of associated factors. There is evidence that one key factor related to food selectivity is sensory overresponsivity (SOR) (Nadon et al, 2011;Smith et al, 2019;Suarez et al, 2012;Zobel-Lachiusa et al, 2015). SOR is defined as an overresponse to sensations that others would not perceive as threatening (Miller, 2014).…”
mentioning
confidence: 99%